Design of pi-controller for stand-alone hydrokinetic energy harnessing - Muhammad Aiman, Azman@Chou Siew Choy (2022)
There are many types of turbines that can be implemented as an energy conversion. However, most of them were applied on dam that need high water flow rates. In this project, the cross flow turbine for hydrokinetic energy harnessing is designed to extract the energy for low speed water velocity. PI-controller is designed to tracking and control due to pattern and variation in water flow, non-linear water velocity and slow tracking response. Besides, monitoring system also designed to check the value of power and current for the hydrokinetic energy harnessing. The improvement of this mechanism will be applied the in rural area. The cross flow water turbine is implemental in the project. The result is show that the output power enough produced by the turbines is sufficient to provide electrical energy for low consumption appliances.